Corporate Social Responsibility Legal Framework in Southeast Asia: Comparing Indonesia, Malaysia, and Thailand - Anggusti, Martono; Dewi Siregar, Fitri Yanni; Chansrakaeo, Ruetaitip (Faculty of Law, Universitas Pattimura, 2025)
Introduction: Corporate Social Responsibility (CSR) has evolved over time, reflecting changes in corporate thinking and practices regarding their relationships with society and the environment.Purposes of the Research: This research aims to analyze the regulation and implementation of CSR in Indonesia to compare it with CSR regulations in other Southeast Asian countries, namely Malaysia and Thailand.Methods of the Research: This research is a normative legal study that emphasizes a conceptual and legislative approach.Results of the Research: The development of the concept of CSR began in the 18th century by Robert Owen, who provided facilities for employees. CSR rapidly evolved in the 20th century, with large companies in the US establishing social departments. Milton Friedman's thinking about profit as the primary goal of business and John Elkington's concept of the